Avian infectious bronchitis virus : ultrastructural pathology of kidney and trachea of chicken infected with local strain of IBV - Arshad, Siti Suri (2001)

(untitled)
(IBV) is prevalent in many countries with an intensive poultry industry. The virus has a significant ecOnomic impact in poultry production. In broiler, production losses are due to poor weight gain, carcass condemnation and mortalily. Whilst in laying chicken, losses are due to sub-optimal egg production and poor quality eggs. In Malaysia, IBV was first reported in 1967 and followed by incidence of nephrosis-nephritis syndrome associated with IBV in 1980. In 1995, a prototype MH5365/95 nephropathogenic IBV strain was isolated. The virus has a tropism towards the epithelial cells. This paper highlighted the ultrastructural pathology of the trachea and kidney of infected chicken by SEM and TEM.